2021
DOI: 10.3390/ijerph18189589
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training Improves Disconnected Limbs’ Mental Representation and Peripersonal Space after Spinal Cord Injury

Abstract: Paraplegia following spinal cord injury (SCI) affects the mental representation and peripersonal space of the paralysed body parts (i.e., lower limbs). Physical rehabilitation programs can improve these aspects, but the benefits are mostly partial and short-lasting. These limits could be due to the absence of trainings focused on SCI-induced cognitive deficits combined with traditional physical rehabilitation. To test this hypothesis, we assessed in 15 SCI-individuals the effects of adding cognitive recovery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 109 publications
(184 reference statements)
1
10
0
Order By: Relevance
“…This supports the idea that sensory information plays a crucial role in bodily self, as shown by studies on deafferented people, in particular individuals suffering from spinal cord injury (SCI; Scandola et al, 2014 , 2017a , 2019b ; Moro et al, 2021a ) or locked-in-syndrome ( Nizzi et al, 2012 ), and recently confirmed by the effects of interoceptive modulations on the sense of body ( Salvato et al, 2017 ; Jenkinson et al, 2020 ; Monti et al, 2020 ; Todd et al, 2021 ).Thus, representations underlying bodily self are the result of a continuous integration of multiple sources of information. This integration process provides immediate feedback on the current state of the body and is also integrated with higher-order cognitive functions (e.g., spatial perception and memory) in order to obtain a detailed map of the body and its relationship with the environment in terms of action planning and motor imagery.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…This supports the idea that sensory information plays a crucial role in bodily self, as shown by studies on deafferented people, in particular individuals suffering from spinal cord injury (SCI; Scandola et al, 2014 , 2017a , 2019b ; Moro et al, 2021a ) or locked-in-syndrome ( Nizzi et al, 2012 ), and recently confirmed by the effects of interoceptive modulations on the sense of body ( Salvato et al, 2017 ; Jenkinson et al, 2020 ; Monti et al, 2020 ; Todd et al, 2021 ).Thus, representations underlying bodily self are the result of a continuous integration of multiple sources of information. This integration process provides immediate feedback on the current state of the body and is also integrated with higher-order cognitive functions (e.g., spatial perception and memory) in order to obtain a detailed map of the body and its relationship with the environment in terms of action planning and motor imagery.…”
Section: Introductionsupporting
confidence: 85%
“…More specifically, the subscale of External Visual Imagery (VMIQ-EVI) necessitates imaging oneself performing actions from a third person perspective (“as if you were watching yourself from an external position”). In contrast, the first person perspective imagery was assessed by means of the Kinesthetic Imagery scale (VMIQ-KIN) with the participants being asked to “imagine feeling themselves performing the movement.” Thus, the two subscales involve different cognitive processes, specifically visual imagery in the case of the former and simulation of bodily sensations for the latter ( Ionta et al, 2010 ; Scandola et al, 2017b ; Moro et al, 2021a ). The vividness of each action that they imagined (12 identical actions in the two subscales) was rated by the participant on a 5-point Likert scale (with 1 = perfectly vivid imagined action and 5 = not imagined at all).…”
Section: Methodsmentioning
confidence: 99%
“…Current treatments for SCI-related neuropathic pain include pharmacological, surgical, electrotherapeutic, physiotherapeutic, and psychological treatments, with only marginal overall benefit. There is also some recent limited, but promising evidence for motor imagery interventions (Moro et al, 2021 ). Austin and Siddall ( 2019 ) published a recent narrative review of virtual reality treatments for SCI pain.…”
Section: Central Neuropathic Painmentioning
confidence: 99%
“…[1][2][3] Increasing evidence shows that adults with SCI with motor and sensory impairments also experience body awareness deficits. [4][5][6][7][8][9][10][11][12][13][14][15] Body awareness refers to an attentional focus on and awareness of internal body sensations, including whole-body awareness as well as awareness of body parts in relation to each other, and how they are positioned and move in space. 16,17 These motor and sensory impairments, and particularly the loss of awareness of where the limbs are in space, 18 greatly compromise function and mobility.…”
Section: Introductionmentioning
confidence: 99%